Pertumbuhan dan Hasil Padi Gogo (Oryza sativa L.) Pada Medium Podsolik (Ultisol) dengan Pemberian Kompos Solid dan Fly Ash Batu Bara - Nursiani Lubis; Stevany Veronica; Nelvia Nelvia; Idwar Idwar; Irfandri Irfandri (Universitas Teuku Umar, 2025)
This research was conducted with the aim of studying the effect of the interaction of solid compost with coal fly ash and each treatment, as well as to obtain the best dose in increasing the growth and yield of upland rice plants (Oryza sativa L.) on Podsolic medium (Ultisol). The study used an experimental method with a completely randomized design (CRD) factorial of two factors, namely the provision of solid compost (0; 2.5; 5; and 7.5 t.ha-¹) and coal fly ash (0; 3; and 6 t.ha-¹) so that 12 treatment combinations were obtained with three replications, totaling 36 experimental units. The soil used was Ultisol soil from Batu Belah Village, Kampar. Observations included growth parameters and yields of upland rice plants of the Inpago 12 variety which included: plant height, maximum and productive number of tillers, panicle emergence age, harvest age, number and percentage of full grain, weight of 1,000 full grain grains, and weight of dry milled grain per clump. The research data were analyzed using analysis of variance (ANOVA) and continued with the Duncan Multiple Range Test (DMRT) at the 5% level. The study showed that there was no interaction between solid compost and coal fly ash on the growth and yield of upland rice (Oryza sativa L.) on Podsolic soil (Ultisol). Solid compost significantly affected several parameters such as plant height, panicle emergence age, harvest age, percentage of full grain, weight of 1000 full grain grains, and weight of dry milled grain per clump with the best dose of 5 t.ha-¹. On the other hand, coal fly ash did not show any significant effect on all observed parameters. Therefore, solid compost at a dose of 5 t.ha-¹ is recommended to increase the growth and yield of upland rice variety Inpago 12 on Podsolic soil (Ultisol).